Cube-and-Conquer for Satisfiability - Oliver Kullmann (Handbook of Parallel Constraint Reasoning, 2018)
The Cube-and-Conquer method is a novel paradigm for distributed SAT solving, combining the old and the new paradigms of SAT solving. Theory and applications are discussed in depth.